White sororities and the cultural work of belonging - Hogg, Charlotte, 1970- author.
1 online resource.
Keywords: "Charlotte Hogg takes a close look, through the example of White university sororities, at how we create and cling to subcultures through the notion of belonging, and how spoken and unspoken rhetorics contribute to this notion. Renewed calls to end Greek-letter organizations for racism and sexism, including increased scrutiny on White women's social justice failings, have intensified. But as Hogg shows, rhetorics of belonging have always occurred amid and even in response to anti-GLO sentiment. She shows how rhetorical efforts by members for members foster belonging for insiders while also seeking to appease those on the outside. In her analysis, Hogg positions the study of rhetoric beyond traditional methods of persuasion to show how we communicate and participate in communities as citizens in subtle ways beyond speaking and writing. Through engaging narrative drawing on her experiences as a member of a White sorority, archival research, and interviews with collegians and alumni, she shows how efforts toward belonging can influence particular beliefs about womanhood in complex ways. This thought-provoking volume will interest scholars and students from a range of disciplines, including rhetoric and communication studies, gender studies, feminism, sociology, cultural anthropology, and history"--